2014
DOI: 10.4236/cn.2014.62009
|View full text |Cite
|
Sign up to set email alerts
|

Internet as a Growing and Dynamic Network: An Economic View

Abstract: The past few decades have witnessed renewed interest and research efforts on the part of the scientific community. After spending decades to disassemble nature, focusing the attention on its components, scientists have shifted their attention on complex networks. These basic structures constitute a wide range of systems in nature and society, but their design is irregular, evolves dynamically over time and their components can fit in a large multiplicity of alternative ways. Nevertheless, the most recent studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It is concluded that this finding is not a fluke but a fact revealed with the author's personal publications in the field of Cardiology. In all probability, this finding is likely to be confirmed by appealing to the Internet itself, seeing that, since RR seems to be taking the back seat nowadays, it is the growing and dynamic network now readily available [19]. Incidentally, by chance, the author obtained through the Internet the citation of his 1972 article [12] by New York workers [20], i.e., a State that lends further weight to Garfield's "clustering" theory [18].…”
Section: Investigationmentioning
confidence: 86%
“…It is concluded that this finding is not a fluke but a fact revealed with the author's personal publications in the field of Cardiology. In all probability, this finding is likely to be confirmed by appealing to the Internet itself, seeing that, since RR seems to be taking the back seat nowadays, it is the growing and dynamic network now readily available [19]. Incidentally, by chance, the author obtained through the Internet the citation of his 1972 article [12] by New York workers [20], i.e., a State that lends further weight to Garfield's "clustering" theory [18].…”
Section: Investigationmentioning
confidence: 86%